Optimalisasi Hasil Belajar Siswa OSIS melalui Manajemen Prioritas dan Pencegahan Prokrastinasi Akademik: Optimization of Student Council Learning Outcomes through Priority Management and Academic Procrastination Prevention - Rotua, Sri Yulina; Nurdianti, Raden Roro Suci; Srigustini, Astri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore preventive strategies to improve Student Council members' learning outcomes by enhancing priority discretion to reduce academic procrastination. This research employs a qualitative approach with a case study method involving Student Council members at SMA Muhammadiyah Tasikmalaya for the 2023/2024 period as the primary subjects. Data were collected through in-depth interviews, observations, and documentation, which were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the primary factors influencing academic procrastination among Student Council members include difficulties in adjusting to tight schedules, poor time management, and a tendency to prioritize more enjoyable activities. The strategies employed by Student Council members to enhance priority discretion include identifying important and urgent tasks, maintaining a daily schedule, and making effective decisions when faced with conflicts between academic and organizational responsibilities. This study concludes that effective priority discretion management plays a crucial role in reducing academic procrastination and improving Student Council members' learning outcomes. The researcher recommends that educational institutions provide time management training for students actively involved in organizations to help them balance academic and organizational responsibilities.may increase the ease with which interested parties can locate our article.